Learning trauma surgery through cytoreductive surgery. Issue 5 (May 2023) - Giudicelli, Xavier; Aoun, Olivier; Perchoc, Amaury; Laville, Victor; Boutonnet, Mathieu; de Carbonnières, Anne; Ezanno, Anne Cécile; Malgras, Brice
Highlights: War surgery requires great surgical versatility. The initial and continuing education of French military gastrointestinal surgeons in war surgery is considered flawed and inappropriate. The low incidence of gastrointestinal trauma in France is not sufficient for training in war surgery. Cytoreductive surgery, which has similarities with war surgery, seems to be an important asset for the initial and continuing education of French military gastrointestinal surgeons. Abstract: Objectives: Regarding war surgery (WS), the initial and continuing education of French military gastrointestinal surgeons (FMGIS) is considered flawed and inappropriate. This results from the low incidence of gastrointestinal (GI) trauma, its predominantly non-surgical management, and a daily surgical practice that strongly differs from WS. Conversely, cytoreductive surgery (CRS) of peritoneal metastases has similarities with WS which led us to assess its potential contribution to the initial and continuing education of FMGIS in WS. Methods: We reported the activities of the GI surgery departments of the military teaching hospitals of Percy and Begin. The first one dedicated to traumatology and the second to CRS. We then specifically looked into the surgical procedures conducted by the FMGIS during deployment from January 2004 to December 2014. Results: Amongst the 600 severe trauma patients admitted to the Percy trauma center between January 2019 and December 2020, 17 underwent abdominal surgery with a total of 25 procedures performed. During the same period, 61 patients undertook CRS in Begin with an average of 7 surgical processes per patient carried out and a total of 418 abdominal surgical procedures. Outside abdominal packing and nephrectomy (not performed in CRS), the numbers of splenectomy, gastrointestinal / gynecological resections (hysterectomy and/or adnexectomy), or liver resection were higher during CRS compared to abdominal trauma surgery with 10 times less patients (10 vs 1, 43 vs 9, 20 vs 0, 6 vs 0, respectively). Conclusion: CRS, through its similarities with WS, seemed to be an appropriate tool for the initial and continuing education of FMGIS in WS and, to an extent, of civilian trauma surgeons who could eventually treat terrorist attacks casualties on the national territory.